Biography of Saidakhmad Vasliy in the Works of his Contemporary of Khodji Muin - Ashurova Xurshida Sag‘dullaevna (Genius Journals, 2022)
In the given article there are a shoot study of life and activitis of Vasliy, his attitudes toward place and role of education system and socio-political life of the time through the prism of looks of other enlightener of his time – Khodji Muin. It is shown that Vasliy in his articles and poems sharply reprobated the system of education in Bukhara which was limited by the studing of religious dogmas
Keywords: life and activity, society, socio-political life, verses and articles, education